Native American Programs Act Amendments of 1983 : hearing before the Subcommittee on Human Resources of the Committee on Education and Labor, House of Representatives, Ninety-eighth Congress, second session, on H.R. 4468 . hearing held in Washington, DC, on March 14, 1984. - United States. Congress. House. Committee on Education and Labor. Subcommittee on Human Resources. (Washington : U.S. G.P.O., 1985)
Distributed to some depository libraries in microfiche. Mode of access: Internet.